1985
DOI: 10.1002/cne.902380105
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the L11 neuropeptide gene in the Aplysia central nervous system

Abstract: Neuron L11 in the abdominal ganglion of Aplysia californica is thought to be both cholinergic and peptidergic. In previous studies, we isolated a cDNA clone encoding the precursor for an L11 secreted protein(s) by differentially screening an abdominal ganglion cDNA library. We now report the isolation of genomic clones encoding the L11 cDNA sequences. Analysis of these clones reveals that the gene is present in a single copy per haploid genome. RNA blotting and cDNA cloning demonstrate that the L11 gene is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…LC-MS/MS analysis of C. gigas neural tissue identified the SPVSLLEQILNNRRRFGL peptide (Additional file 2 ), indicating that this is probably a bioactive peptide released from the precursor. Elevenin-like precursors have been described in Lottia gigantea [ 12 ] and Aplysia [ 48 ], while a similar precursor from the pygmy squid Idiosepius and nematode Caenhorabditis elegans are present within the NCBI Genbank database. Comparison of the oyster elevenin precursors with other molluscs and worms shows little overall conservation, even within the elevenin mature peptide, however, there is conservation of cysteine residues at positions 5 and 14.…”
Section: Resultsmentioning
confidence: 99%
“…LC-MS/MS analysis of C. gigas neural tissue identified the SPVSLLEQILNNRRRFGL peptide (Additional file 2 ), indicating that this is probably a bioactive peptide released from the precursor. Elevenin-like precursors have been described in Lottia gigantea [ 12 ] and Aplysia [ 48 ], while a similar precursor from the pygmy squid Idiosepius and nematode Caenhorabditis elegans are present within the NCBI Genbank database. Comparison of the oyster elevenin precursors with other molluscs and worms shows little overall conservation, even within the elevenin mature peptide, however, there is conservation of cysteine residues at positions 5 and 14.…”
Section: Resultsmentioning
confidence: 99%
“…LJ cluster 1 is also the only LJ cluster comprising cells containing peptides from the prohormone L11 (P06518). As with R3-14, L11 has been localized to the abdominal ganglion using Northern blot and IHC ( 86 ). Consistent with these data, the colocalized detection of peptides from these two prohormones is found in LJ cluster 1, which has the greatest percentage of and contains more abdominal ganglion cells than any other LJ cluster ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the LUQ-1 and L5-67 gene products are not the only neuropeptides to be found differentially in LUQ cells. Indeed, Taussig, Kaldany, Rothbard, Schoolnik, and Scheller, ( 1985) have reported that Aplysia L11 neuropeptides were also expressed in two (or three) of the four dorsal LUQ cells, suggesting a further specialization of these cells. It will be important to map precisely the axonal networks generated by the five cells in order to determine the specific targets of each of these cells and to see how the different phenotypes are related to different physiological properties.…”
Section: Cellular Distribution Of Luq Neuropeptidementioning
confidence: 97%